The Impact of Covid-19 on Ready-to-Drink Coffee Consumer Behavior for People in Situbondo - Afri Prayudi; Yuli Hariyati; Evita Soliha Hani (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
Drinking coffee has become a lifestyle for students. Various coffee drinks are available, including coffee-processed and instant coffee. Instant coffee In December 2019, the COVID-19 disease epidemic appeared, which changed the behaviour of coffee consumers. The purpose of the study was to find out the effect of the disease after COVID-19 on the behaviour of instant coffee consumers in Situbondo, to find out the effect of lifestyle on the behaviour of instant coffee consumers in Situbondo and to identify the effect. Post-COVID-19 edition of Situbondo instant coffee consumer lifestyle. This research method is a kind of quantitative descriptive research, and the data analysis method is Partial Least Square (PLS). The variables of this research are: after covid-19 (X1), lifestyle (X2) and consumer behavior (Y1). The results of this study are as follows: After Covid-19 (X1) has a significant effect on consumer behavior (Y1) with a positive original sample value (0.77) with a p-value of 0.000 (<0.05) and t. -statistics of 12.49 (>1,96), lifestyle (X2) has no significant effect on consumer behavior (Y1), the original sample value is positive (0.13) with a p-value of 0.09 (>0.05), and t Statistic 1.72 (<1,96) and post-Covid-19 (X1) has a significant impact on lifestyle (X2), with the original sample value being positive (0.64) with a p-value of 0.000 (<0.05) and a t-statistic of 8.00 (>1,96). This study concludes that post-Covid-19 has a significant effect on consumer behaviour (H1 accepted), lifestyle does not have a significant effect on consumer behaviour (H2 rejected) and post-Covid-19 effect on lifestyle (H3 taken)